(untitled) (LEARNing Landscapes, 2021)
Drawing upon my experience as a Canadian Muslim woman, scholar, educator, and mother, I share and inquire into my stories of experiences alongside youth. Thinking narratively (Clandinin, 2013), I weave my experiences using and teaching with/about single stories (Adichie) and counterstories (Lindemann Nelson, 1995) alongside students to (re)shape the multiplicity of ourselves (Lugones, 1987), relationships, and communities. This article will provide windows, mirrors, and sliding glass doors (Bishop, 1990) into my school and familial curriculum-making (Huber, Murphy, & Clandinin, 2011) experiences alongside Muslim youth. I hope that it will also provide insights into the experiences of diverse Muslim children, youth, and caregivers/families.